Using novel methods to track British and Irish Ice Sheet dynamics since the Late Pleistocene, along the west Porcupine Bank, NE Atlantic. (15th May 2022) - O'Reilly, Luke; Lim, Aaron; Titschack, Jürgen; Moore, Niamh; O'Connor, O.J.; Appah, John; Fentimen, Robin; Butschek, Felix; Harris, Kimberley; Vennemann, Torsten; Wheeler, Andrew J.
Abstract: Extensive research has been undertaken to elucidate the glacial history of the British Irish Ice Sheet (BIIS) in the NE Atlantic. BRITICE-CHRONO has compiled terrestrial and marine based evidence, to provide an empirical reconstruction of ice sheet expansion and retreat during the Late Pleistocene. Across the Irish margin, particular focus has been given to seafloor sediments which contain ice-rafted debris (IRD). However, there are few publications on IRD from areas proximal to the maximum extent of the BIIS, which would offer further insights on the behaviour of the ice sheet during (de)glacial events. Previous exploratory surveys of the west Porcupine Bank (wPB) visually identified IRD on the seafloor and these present a new study site to investigate the extent of the BIIS and the course of its icebergs. Moreover, there are uncertainties about the effects of icebergs on the marine life and cold-water corals occupying the nearby Porcupine Bank Canyon. Assessing a sediment core containing an IRD analogue for the wPB would thus, have a dual purpose. In the past however, coring missions of the wPB using traditional coring methods (i.e. piston and gravity cores) were unsuccessful. Here, we utilized a novel ROV-mounted vibrocoring procedure to capture a 0.75 m IRD-bearing sediment core from the wPB. Then further novel analytical methods (computed tomography-based IRD-detection) were used to quantify IRD every 0.02 cm to provide the highest resolution record of BIIS related IRD to date. From this, several fluxes of IRD deposition onto the wPB between 31.6 and 9 ka BP were revealed and corroborated by other published records from across the NE Atlantic. It was shown that the wPB IRD fluxes occur simultaneously with other parts of the margin. The IRD signal also shows that iceberg calving occurred on the wPB during the Younger Dryas. Grain-size analysis of the core allowed for a reconstruction and interpretation of the palaeoenvironmental conditions during these IRD flux events and shows that BIIS-derived glaciers had a major impact on hydrodynamic conditions in the wPB. Subsequently, intensive scouring led to a major hiatus in the core during 27.3–17.2 ka BP. These results are a useful addition to BIIS literature on this part of the shelf. Furthermore, it shows that bottom currents were influenced by (de)glacial events, an important finding when considering the presence of nearby current-dependant benthos. Highlights: New methods provide 0.02 cm resolution BIIS derived IRD estimation First use of ROV-mounted vibrocoring in BIIS study wPB IRD fluxes coeval with other NE Atlantic records IRD was delivered to the wPB during the Younger Dryas Major 10.1 ka unconformity identified in the core between 27.3 and 17.2 ka BP